PetriJet Platform Technology: An Automated Platform for Culture Dish Handling and Monitoring of the Contents. (August 2015) - Vogel, Mathias; Boschke, Elke; Bley, Thomas; Lenk, Felix
Due to the size of the required equipment, automated laboratory systems are often unavailable or impractical for use in small- and mid-sized laboratories. However, recent developments in automation engineering provide endless possibilities for incorporating benchtop devices. Here, the authors describe the development of a platform technology to handle sealed culture dishes. The programming is based on the Petri net method and implemented via Codesys V3.5 pbF. The authors developed a system of three independent electrical driven axes capable of handling sealed culture dishes. The device performs two difference processes. First, it automatically obtains an image of every processed culture dish. Second, a server-based image analysis algorithm provides the user with several parameters of the cultivated sample on the culture dish. For demonstration purposes, the authors developed a continuous, systematic, nondestructive, and quantitative method for monitoring the growth of a hairy root culture. New results can be displayed with respect to the previous images. This system is highly accurate, and the results can be used to simulate the growth of biological cultures. The authors believe that the innovative features of this platform can be implemented, for example, in the food industry, clinical environments, and research laboratories.